À quelles conditions l'entretien d'inspection des enseignants du second degré peut-il devenir source de développement professionnel ? Rôle de la réflexivité des acteurs - Bernadette Voisin-Girard; Stéphane Talérien; Stefano Bertone (Nantes Université, 2021)
This study aims to shed light on the nature of the judgemental activity of the Inspectors of académy, Régional Pedagogical Inspectors deployed within the individual inspection interviews of experienced secondary school teachers in order to identify the conditions for the development of professionals in this context. As part of an anthropocultural technological research programme, this research mobilises a plural theoretical framework: the philosophy of language, the theory of dialogue and the clinic of activity in order to understand and encourage the professional development of the actors. The results show 1) a synoptic view of the language games of the inspectors allowing to understand the conditions of development of the interviewing teachers and of the inspectors through the access to their practice, and 2) the reflexive development of a collective of inspectors through the emergence of fruitful alternatives in front of professional dilemmas.